The effects of silica aerogel on the rheological behaviour and polymer matrix structure of Rigid Polyurethane foams. (5th August 2022) - Cimavilla-Román, Paula; Perez-Tamarit, Saul; Vananroye, Anja; Moldenaers, Paula; Ángel Rodriguez-Pérez, Miguel
Graphical abstract: Highlights: Rigid polyurethane-aerogel foams are produced using isocyanate-aerogel dispersions of different concentrations. Rheology shows that for concentrations above 2.5 wt% of aerogel the dispersion is in a percolated gel-like state. The addition of aerogel progressively slows down the viscosity build-up and curing of the foam. Percolated dispersions show less drainage of the reactive polymer and, in turn, lower fraction of mass in the struts of the final foam. Abstract: The incorporation of silica aerogel particles into the isocyanate used to prepare Rigid Polyurethane composite foams drastically modifies its rheological behaviour. The isocyanate changes from being a Newtonian fluid of constant viscosity (0.3 Pa s at 25 °C) to a non-linear power-law material with complex viscosity decreasing from 10 4 to 10 1 Pa s with a slope −1 versus frequency. The change in response is caused by the formation of a percolated network of particles at contents above 2.5 wt% of aerogel. Moreover, the addition of aerogel significantly slows down the modulus-build up kinetics and vitrification of the matrix by approximately 4.5 min with every 1 wt% of aerogel added. For the foam with 3.0 wt% of aerogel, the combination of high viscosity at early reaction times coupled with the slow modulus build-up impedes the drainage which leads to a decrease in the fraction of material in the struts of the matrix.